2007
DOI: 10.1021/np070583r
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic Effect of Natural Galphimines from Galphimia glauca and their Chemical Derivatives

Abstract: [435][436][437][438][439][440][441][442][443][444]. In this regard, compound 1, named shearinine D, is identical to the compound with the same name in this article, and compound 3, named shearinine F, is identical to shearinine K reported by this group. The authors apologize for any inconvenience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this context, Herrera-Ruiz et al tested the anxiolytic properties of goldshower using the EPM test with different sets of mice. They found that the galphimine-rich fraction, galphimine A, and galphimine B showed a higher anxiolytic effect than the placebo, but this effect was modest compared to the standard drug [56]. These same authors [57] studied the effects of a standardized extract using the EPM, the light-dark test, and the forced swimming test in mice and observed an anxiolytic-like effect in the EPM and the light-dark tests; however, no effect was observed in the forced swimming test.…”
Section: Galphimia Glaucamentioning
confidence: 99%
“…In this context, Herrera-Ruiz et al tested the anxiolytic properties of goldshower using the EPM test with different sets of mice. They found that the galphimine-rich fraction, galphimine A, and galphimine B showed a higher anxiolytic effect than the placebo, but this effect was modest compared to the standard drug [56]. These same authors [57] studied the effects of a standardized extract using the EPM, the light-dark test, and the forced swimming test in mice and observed an anxiolytic-like effect in the EPM and the light-dark tests; however, no effect was observed in the forced swimming test.…”
Section: Galphimia Glaucamentioning
confidence: 99%
“…164,165 Galphimines have also been chemically modified via medicinal chemistry, furthering the understanding of some structure− activity relationships. 166 This general methodology (Figure 7) has been used since in several cases to identify bioactive compounds, and we will now highlight some very recent examples. Briefly, the first step is obtaining a sufficient number of samples, either by collecting samples from different locations, different plant parts, or closely related species, or by applying numerous, slightly different extraction steps.…”
Section: ■ Metabolomics For the Discovery Of Drugs From Natural Sourcesmentioning
confidence: 99%